2013
DOI: 10.1007/jhep02(2013)065
|View full text |Cite
|
Sign up to set email alerts
|

Singularities in K-space and multi-brane solutions in cubic string field theory

Abstract: In a previous paper [arXiv:1111.2389], we studied the multi-brane solutions in cubic string field theory by focusing on the topological nature of the "winding number" N which counts the number of branes. We found that N can be nontrivial owing to the singularity from the zero-eigenvalue of K of the KBc algebra, and that solutions carrying integer N and satisfying the EOM in the strong sense is possible only for N = 0, ±1. In this paper, we extend the construction of multibrane solutions to |N | ≥ 2. The soluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 26 publications
4
62
0
1
Order By: Relevance
“…Though the configuration (1.2) is a pure-gauge one and formally satisfies the EOM, Q B Ψ + Ψ 2 = 0, (1.5) this is in fact a subtle problem due to the singularity at K = 0. As the requirements on the pure-gauge configuration Ψ (1.2) as a solution, the number of D25-branes Ψ represents and the EOM test of Ψ against itself were examined for various G(K) defining U [5,6,7,8]. For calculating these quantities, we have to regularize the singularity at K = 0.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the configuration (1.2) is a pure-gauge one and formally satisfies the EOM, Q B Ψ + Ψ 2 = 0, (1.5) this is in fact a subtle problem due to the singularity at K = 0. As the requirements on the pure-gauge configuration Ψ (1.2) as a solution, the number of D25-branes Ψ represents and the EOM test of Ψ against itself were examined for various G(K) defining U [5,6,7,8]. For calculating these quantities, we have to regularize the singularity at K = 0.…”
Section: Introductionmentioning
confidence: 99%
“…The EOM test is also passed, namely, T = 0 in these two cases. It was shown that the origin of non-trivial N in these solutions is the singularity coming from the zero or pole of G(K) at K = 0 [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More surprisingly, it is possible to generalize this into an automorphism group of the KBc subalgebra [21]. Applications of this symmetry have been discussed in [13,[20][21][22][23][24][25][26]. Here we show that the automorphisms can be further extended to act on boundary condition changing operators.…”
Section: Taming Anomaliesmentioning
confidence: 80%
“…For the purposes of the present discussion we leave these subtleties to the side, and proceed under the assumption that the spectrum of K is real and non-negative. 8 There has been interesting discussion of diffeomorphisms of the spectrum of K which are not homotopic to the identity, generated by the transformation K → 1/K [20]. The resulting automorphisms are singular, and we will not consider them.…”
Section: Taming Anomaliesmentioning
confidence: 99%